Прогностичне значення додаткових хромосомних аномалій у Ph позитивних клітинах кісткового мозку при хронічний мієлоїдній лейкемії - Лозинська, М.Р.; Масляк, З.В.; Лукавецький, Л.М.; Цяпка, О.М.; Лозинський, Р.Ю. (Цитология и генетика, 2005)
Изучалось прогностическое значение сочетания разных хромосомных аномалий, а также геномных мутаций у Ph+-пациентов с хронической миелоидной лейкемией. Проведено 49 цитогенетических исследований аспирата костного мозга от 35 пациентов (11 обследовано в динамике). Добавочные аномалии хромосом выявлены в 25,07 % случаев, причем приблизительно 80 % аномалий появлялись на стадии бластного кризиса (БК). Для стадии БК характерной добавочной аномалией хромосом была extra Ph-хромосома, трисомия 8-й и 19-й хромосом. Негативное прогностическое влияние на протекание ХМЛ имело появление клонального разнообразия клеток, повышенной частоты геномных мутаций и микрохромосом. We studied the prognostic significance of combination of different chromosomal abnormalities and genomic mutations in Ph+ chronic myeloid leukemia patients. In general 49 cytogenetic analyses of bone marrow aspirate from 35 patients (11 of these observed in dynamics) have been carried out. The additional chromosome changes were found in 25,07 % cases and approximately 80 % of anomalies appeared in the blast phase. Among the secondary chromosomal abnormalities extra Ph-chromosome appeared mostly in different combinations with trisomy of chromosomes 8 and 19. Appearance of clonal differences of cells, high rate of genome mutations and of microchromosomes had negative prognostic significance on disease proceeding.